Phthalate exposure increases subclinical atherosclerosis in young population. (July 2019) - Su, Ta-Chen; Hwang, Jing-Shiang; Torng, Pao-Ling; Wu, Charlene; Lin, Chien-Yu; Sung, Fung-Chang
Abstract: The link between phthalate exposure and the risk of subclinical atherosclerosis in young population remains unclear. This study investigated the association between phthalate exposure and subclinical atherosclerosis, in terms of carotid intima-media thickness (CIMT), in young population. From a nationwide mass urine screening for renal health, conducted in 1992–2000 among school children 6–18 years of age in Taiwan, we recruited 789 subjects to participate in the cardiovascular health examination in 2006–2008. Among them, 787 received measurements of 7 urinary phthalate metabolites and CIMT. Results showed both mean and maximal values of CIMT at all segments of carotid arteries significantly increased with the urinary mono-2-ethylhexyl phthalate (MEHP), ∑ di-(2-ethylhexyl) phthalate (DEHP), and mono-n-butyl phthalate (MnBP) in a dose-response relationship after adjustment for multiple linear regression models. Multivariate logistic regression analysis showed that higher quartiles of urinary concentrations of MEHP, ∑DEHP, and MnBP were associated with a higher risk of thicker CIMT. Compared to subjects with the lowest quartile (Q1) of urinary MEHP, the adjusted odds ratios (95% confidence interval) for thicker CIMT among subjects with higher urinary MEHP were 2.13 (1.18–3.84) at Q2, 4.02 (2.26–7.15) at Q3 and 7.39 (4.16–13.12) at the highest Q4. In conclusion, urinary phthalate metabolites of MEHP, ∑DEHP, and MnBP are strongly associated with CIMT in adolescents and young adults in Taiwan. Graphical abstract: Image 1 Highlights: Demonstrate urinary metabolites of DEHP and DiBP are significantly and positively associated with CIMT in young population. A dose-response relationship between phthalate exposure and CIMT at all segments of extracranial carotid bed. Preventing phthalate exposure is important for primary prevention of atherosclerotic disease. Abstract : Phthalate exposure increased subclinical atherosclerosis in young population indicated the atherogenic potential of DEHP and MnBP.